Timing the r-process Enrichment of the Ultra-faint Dwarf Galaxy Reticulum II - Joshua D. Simon; Thomas M. Brown; Burçin Mutlu-Pakdil; Alexander P. Ji; Alex Drlica-Wagner; Roberto J. Avila; Clara E. Martínez-Vázquez; Ting S. Li; Eduardo Balbinot; Keith Bechtol; Anna Frebel; Marla Geha; et al. (The Astrophysical Journal, 2023)
The ultra-faint dwarf galaxy Reticulum II (Ret II) exhibits a unique chemical evolution history, with ${72}_{-12}^{+10}$ % of its stars strongly enhanced in r -process elements. We present deep Hubble Space Telescope photometry of Ret II and analyze its star formation history. As in other ultra-faint dwarfs, the color–magnitude diagram is best fit by a model consisting of two bursts of star formation. If we assume that the bursts were instantaneous, then the older burst occurred around the epoch of reionization, forming ∼80% of the stars in the galaxy, while the remainder of the stars formed ∼3 Gyr later. When the bursts are allowed to have nonzero durations, we obtain slightly better fits. The best-fitting model in this case consists of two bursts beginning before reionization, with approximately half the stars formed in a short (100 Myr) burst and the other half in a more extended period lasting 2.6 Gyr. Considering the full set of viable star formation history models, we find that 28% of the stars formed within 500 ± 200 Myr of the onset of star formation. The combination of the star formation history and the prevalence of r -process-enhanced stars demonstrates that the r -process elements in Ret II must have been synthesized early in its initial star-forming phase. We therefore constrain the delay time between the formation of the first stars in Ret II and the r -process nucleosynthesis to be less than 500 Myr. This measurement rules out an r -process source with a delay time of several Gyr or more, such as GW170817.